Using time dynamically in static intervals: Does it close the achievement gap? - Grace, Lori (Learning Environments Research, 2017)
A mixed-methods study was undertaken with 118 biology students in two urban high schools. A Student-Centered Adaptable Learning Environment (SCALE) was created to improve engagement from affective and cognitive perspectives using choice, creativity and technological allowances. Results demonstrated that fast and slow learners are generally separated by about 30 min in terms of inputting speeds, but can be as much as 65 min apart from one another. Given that traditional classrooms afford students only 45 min in which to learn, static time could have become a source of inequity in public schools. SCALE optimally allowed for the dynamic use of time in constrained periods, therefore reducing and even eliminating any negative relationships between speed of learning and resultant achievement gains in the block setting. Especially benefitting from their ability to maneuver were the slowest learners, who showed the largest achievement improvements in either time interval amongst ability groupings. As learning speed can be the most critical contributing component of resultant educational outcomes, providing students the ability to use time dynamically should be considered as a feasible solution to helping teachers reestablish equity in mixed-ability classrooms in public schools. © 2017, Springer Science+Business Media Dordrecht.
Keywords: Cognitive levelling; Dynamic time; Educational technology; Learning equity; Learning speed gap; Psychosocial learning environments; dept.bio

The marginalization of the “any” learner - Grace, Lori (Journal of Educational Leadership and Policy Studies, 2017)
Keywords: dept.edl